Surgical treatment of primary cardiac tumors: an eleven-year experience of a single center (Annals of Medical Research, 2021)
Aim: We aimed to report our surgical experience about cardiac tumors in our hospitalMaterial and Methods: The study enrolled 25 patients who underwent cardiac surgery for cardiac tumors between June 2009 and June 2019. Baseline clinical features, symptoms of the patients, localizations of the tumors and surgical notes of the patients were recorded.Results: In 22 of 25 patients, histopathologic result was atrial myxoma. The other three tumors were hibernoma, papillary fibroelastoma and angiosarcoma. Hibernoma was in interatrial septum, papillary fibroelastoma was on subvalvular surface of aortic valve and angiosarcoma was in right atrium invading into right ventricle. We experienced our own recurrence in one patient, also re-operated another patient who underwent the first operation in a different hospital. No death and major complication occurred during post-operative period.Conclusion: Surgical removal of the cardiac tumors is an effective treatment with low complication and recurrence rates.
Keywords: Cardiac tumor; myxoma; neoplasm; surgery